The First Steps of Renal Transplants in Mexico - Viesca, Carlos A.; Ramos R. de Viesca, Maríablanca (DELTOS, 2025)
Following the first successful kidney transplants performed by Joseph Murray and John Merrill in 1954, Mexican physicians and researchers began their own work in the field. Prompted by developments abroad, they engaged in theoretical study, laboratory research, and experimental procedures. In 1962, José Carlos Peña established Mexico’s first chronic haemodialysis programme at the Hospital de Enfermedades de la Nutrición, followed shortly by an intraperitoneal dialysis programme. That same year, the country’s first kidney transplant from a living donor was performed by Manuel Quijano Narezo and Federico Ortiz Quezada. Two years later, the first transplant in an adult patient was conducted, and in 1967, the first procedure involving a cadaveric donor took place. A formal renal transplant programme was finally established in 1975 at the Mexican Institute of Social Security (IMSS).